Diversity in Cybersecurity. - Knight, John; Davidson, Jack; Nguyen-Tuong, Anh; Hiser, Jason; Co, Michele (Computer (00189162), 2016)
Randomizing software characteristics can help thwart cyberattacks by denying critical information about a target system previously known to an attacker.